Crucial role of the melanocortin receptor MC1R in experimental colitis. Issue 10 (16th March 2006) - Maaser, C; Kannengiesser, K; Specht, C; Lügering, A; Brzoska, T; Luger, T A; Domschke, W; Kucharzik, T
Abstract : Background and aims: α-Melanocyte stimulating hormone (αMSH) is known to exert anti-inflammatory effects, for example in murine DSS (dextran sodium sulphate induced) colitis. The anti-inflammatory functions of αMSH are mediated by the melanocortin1-receptor (MC1R) in an autoregulatory loop. The aim of this study was therefore to determine whether a breakdown of the αMSH–MC1R pathway leads to worsening of disease. Methods: Experimental colitis was induced in mice with a frameshift mutation in the MC1R gene (MC1Re/e), C57BL/6 wild type mice, and MC1Re/e-C57BL/6 bone marrow chimeras. The course of inflammation was monitored by weight loss, histological changes in the colon, and myeloperoxidase activity. In addition, MC1R expression was analysed in intestinal epithelial cells. Results: While the colon of untreated MC1Re/e appeared normal, the course of DSS-colitis in MC1Re/e mice was dramatically aggravated, with a significantly higher weight loss and marked histological changes compared to C57BL/6WT. The inflammation eventually led to death in all MC1Re/e, while all C57BL/6WT survived. Similar observations were detected in a transmissible murine colitis model induced by Citrobacter rodentium . Infected MC1Re/e showed delayed clearance of infection. To determine whether missing haematopoietic cell expressed MC1R was responsible, DSS colitis was induced in MC1Re/e-C57BL/6 bone marrow chimeras. MC1Re/e mice receiving MC1R+ bone marrow showed a similar course of inflammation to non-transplanted MC1Re/e. Likewise, transplantation of MC1R bone marrow into C57BL/6WT mice did not lead to any worsening of disease. Conclusions: This is the first study to show a functional role of MC1R in intestinal inflammation. The data suggest a pivotal role of non-haematopoietic cell expressed MC1R in the host's response to pathogenic stimuli.